Trophic state of the Tanjung Putus Lake, Siak Hulu District, Kampar Regency, Riau Province based on Trophic States Index - Agustri Minggu Samosir Minggu Samosir; Tengku Dahril; Asmika H Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTMany activities in Tanjung Putus Lake Buluh Cina Village, Kampar District, Riau contributed the input of organic and anorganic matter that affectsthe water quality, especially nutrient concentration in waters. A research aims to understand the trophic state of Tanjung Putus Lake, Buluh Cina Village, Kampar District, Riau based on TSI has been conducted on March, 2018. There were 3 station namely station 1 (inlet area), station 2 (in the middle of lake) and station 3 (outlet area). In each stations, there were 2 sampling sites, in the surface and in the middle of water column. Sampling was done three times, onces a week. Water quality parameters measured were transparency, temperature, pH, dissolved oxygen, phosphate and nitrate concentration. Results shown that transparency : 85.17 – 96.50 cm, total phosphorus : 100.3 – 143.8 µg/L, chlorophyll-a : 6.406 – 8.497 µg/L, depth :160 cm – 250cm, temperature 30.2 – 31.8 ºC, 5, dissolved oxygen 4.82 – 6.48 mg/L and nitrate : 0.04 – 0.06mg/L TSI value (60.352-66.61). Based on the TSI of Tanjung Putus Lake was categorized as light eutrophic. Keywords:Tanjung putus lake, water quality, eutrophic